Discourse: A critical introduction - Blommaert, Jan (Cambridge University, 2013)
This new introduction offers a critical approach to discourse, written by an expert uniquely placed to cover the subject for a variety of disciplines. Organised along thematic lines, the book begins with an outline of the basic principles, moving on to examine the methods and theory of CDA (critical discourse analysis). This concise introduction will be welcomed by students and researchers in a variety of disciplines involved in the study of discourse, including linguistics, linguistic anthropology and the sociology of language.